Alteration and Restoration of Endotoxin Activity after Complexing with Plasma Proteins - Rudbach, Jon A. (1966)
Rudbach, Jon A. (The University of Michigan, Ann Arbor), and Arthur G. Johnson. Alteration of endotoxin activity after complexing with plasma proteins. J. Bacteriol. 92:892–898. 1966.—A substantial decrease in the ability of endotoxin to be precipitated by homologous antiserum and to cause fever occurred after incubation with human plasma or human plasma, Cohn fraction IV-1. The endotoxin, thus altered, also displayed decreased lethality for rabbits. These alterations in endotoxin activity could be restored when the endotoxin-plasma protein mixture was treated with a proteolytic enzyme, and the endotoxin was precipitated with ethyl alcohol. Inactivation of the antigenic and toxigenic properties of the endotoxin molecule by plasma is discussed as resulting from complexing with plasma proteins rather than from enzymatic degradation.